THE MUSLIM AND THE JEW: A STUDY OF JOHN UPDIKE’S TERRORIST - Doha Al-Sayed (Social Sciences, Humanities and Education Journal (SHE Journal), 2021)
The perception of Muslims and Islam has changed after the attacks on the World Trade Center on September 11th 2001. Muslims have been projected as essential and natural-born terrorists. Thus, authors have taken this projection and reflected it into their works. John Updike, in his novel Terrorist, has done the same. He has portrayed two characters, a Muslim and a Jew. The contrast between the two characters reinforces the Islamophobic concerns of Western audience, in general, and ,American audience, in particular. Through lexical choices, narration technique, motifs and symbolism, Updike manages to further cast away the Muslim character from his society. Therefore, this research paper examines the Islamophobic, Orientalist aspects represented in Updike's Terrorist, through the comparison made between the .Egyptian-American, Muslim Ahmad, and the American, Jewish Levy.